'English Bess' abroad: piracy, politics, and gender in the plays of Thomas Heywood. (2nd July 2016) - Jones, Sue
ABSTRACT: This article considers three plays on the theme of piracy written by Thomas Heywood between 1597 and 1631: The fair maid of the west, part I and part II, and Fortune by land and sea (co-authored with William Rowley). Though all of these plays are set during the reign of Elizabeth I, only The fair maid of the west, part I was written during her lifetime, the two later works being written during the reigns of her successors, James I and Charles I. These plays can be read as a vehicle by which the very different attitudes towards piracy, foreign policy, and national expansion demonstrated by the three consecutive monarchs were interrogated, contrasted, and critiqued. Considered separately each of these works offers a snapshot of the popular view of piracy and privateering at the time of writing; read together they give a much broader insight into contemporary attitudes towards the evolution of England as a maritime power.